A Novel Complex Mutant β-Lactamase, TEM-68, Identified in a Klebsiella pneumoniae Isolate from an Outbreak of Extended-Spectrum β-Lactamase-Producing Klebsiellae - Fiett, Janusz (American Society for Microbiology, 2000)
Twenty-two Klebsiella pneumoniae and two K. oxytoca extended-spectrum β-lactamase (ESBL)-producing isolates were collected in 1996 from patients in two pediatric wards of the University Hospital in Wrocław, Poland. Molecular typing has revealed that the K. pneumoniae isolates represented four different epidemic strains. Three kinds of enzymes with ESBL activity (pI values of 5.7, 6.0, and 8.2) were identified. The pI 6.0 β-lactamases belonged to the TEM family, and sequencing of the bla(TEM) genes amplified from representative isolates revealed that these enzymes were TEM-47, previously identified in K. pneumoniae isolates from pediatric hospitals in Łódź and Warsaw. One of the TEM-47-producing strains from Wrocław was very closely related to the isolates from the other cities, and this indicated countrywide spread of the epidemic strain. The pI 5.7 β-lactamase was produced by a single K. pneumoniae isolate for which, apart from oxyimino-β-lactams, the MICs of β-lactam–inhibitor combinations were also remarkably high. Sequencing revealed that this was a novel TEM β-lactamase variant, TEM-68, specified by the following combination of mutations: Gly238Ser, Glu240Lys, Thr265Met, and Arg275Leu. The new enzyme has most probably evolved from TEM-47 by acquiring the single substitution of Arg275, which before was identified only twice in enzymes with inhibitor resistance (IR) activity. TEM-68 was shown to be a novel complex mutant TEM β-lactamase (CMT-2) which combines strong ESBL activity with relatively weak IR activity and, when expressed in K. pneumoniae, is able to confer high-level resistance to a wide variety of β-lactams, including inhibitor combinations. This data confirms the role of the Arg275Leu mutation in determining IR activity and documents the first isolation of K. pneumoniae producing the complex mutant enzyme.